Peningkatan Self-confidence Siswa melalui Layanan Bimbingan Kelompok Teknik Reframing - Ayuni, Putri; Karamoy, Yurike Kinanthy; Triana, Dian (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
Someone with high self-confidence tends to believe they can find answers to the obstacles they face. On the other hand, individuals with low self-confidence will feel that they cannot solve the problems they face. Based on the phenomenon found at SMPN 02 Silo school, some students have low levels of self-confidence, including being nervous when meeting new people, shy when asked questions, and not daring to express opinions. With this phenomenon, the research aims to increase students' self-confidence. The research method uses a qualitative approach with a PTBK design. The respondents studied were 28 students, with 6 students selected using purposive sampling as samples. The data collection method was carried out using a questionnaire. From the results of observations of the service action process, it was discovered that the level of student self-confidence increased in each research cycle, in cycle I it reached a percentage of 66% of the sample in the medium category (81-120), then in the second cycle the percentage of students had reached 83% of the sample in the high category (121-160), so it can be said that providing guidance services for the reframing technique group was able to increase the self-confidence of class VIII B students at SMPN 02 Silo. __________________________________________________________________Seseorang dengan Self-confidence tinggi cenderung yakin bahwa mereka mampu untuk mencari jawaban atas kendala yang mereka hadapi. Sebaliknya, seseorang dengan Self-confidence rendah sering merasa tidak mampu untuk menyelesaikan masalah yang dihadapi. Berdasarkan fenomena yang ditemukan di sekolah SMPN 02 Silo bahwa sebagian siswa memiliki tingkat Self-confidence yang rendah diantaranya gugup ketika bertemu orang baru, malu ketika ditanya, serta tidak berani mengungkapkan pendapat. Dengan adanya fenomena tersebut maka tujuan penelitian adalah untuk meningkatkan Self-confidence siswa. Metode penelitian menggunaakan pendekatan kualitatif dengan desain PTBK. Responden yang diteliti berjumlah 28 siswa, dengan 6 siswa dipilih secara purposive sampling sebagai sampel. Metode pengumpulan data dilakukan dengan kuesioner. Pada hasil pengamatan proses tindakan layanan diketahui bahwa tingkat Self-confidence siswa meningkat pada tiap siklus penelitian, pada siklus I mencapai persentase 66% sampel dalam kategori sedang (81-120), kemudian pada siklus ke II persentase siswa telah mencapai 83% sampel dalam kategori tinggi (121-160), Hal ini menunjukkan bahwa penerapan layanan bimbingan kelompok teknik reframing mampu meningkatkan Self-confidence siswa kelas VIII B SMPN 02 Silo.